Analisis Faktor Pengaruh Shift Kerja Terhadap Tingkat Produktivitas Kerja Pada Operator SPBU Di Banda Aceh Tahun 2022 - Sri Yuliza; Vera Nazhira Arifin; Putri Ariscasari (CV. Pusdikra Mitra Jaya, 2023)
Productivity is an important indicator in economic activity. Productivity as leverage for national economic growth in the long run. This is one of the reasons many countries are competing to increase their productivity. Indonesia is recorded to have a low level of worker productivity within the Asian region. Increasing labor productivity can increase income so that welfare can be achieved. In addition, labor productivity is also an indicator to achieve high competitiveness. The purpose of this study was to determine the effect of work shifts, workload, work discipline, work experience, age, gender, length of service, and work environment on work productivity at gas station operators in Banda Aceh City in 2022. This research is descriptive analytic with cross sectional design. The population in this study were all gas station operators in Banda Aceh City, namely 32 people. Sample. Data collection was carried out for 6 days from 12 to 17 February 2022 using a questionnaire. Bivariate data analysis using the Logistic Regression test with the Stata 12 computer program. The results showed that the work productivity of gas station operators was more bad, namely 59.38% compared to good ones, which was 40.63%. The results of the logistic regression test showed that there was an effect of workload (p value=0.001), work discipline (p value=0.001), years of service (p value=0.03), and work environment (p value=0.008) on work productivity. Meanwhile, work shift (p value=0.34 and OR=0.5), age (p value=0.17 and 0.09), and gender (p value=0.17) did not affect work productivity.